Nurturing Sustainable Development: Unveiling the Dynamics of Implementing Slum Management Policies in Indonesia - Ida Nuryadi; Dahyar Daraba; Sampara Lukman; Eko Budi Santoso (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This article explores the dynamics of implementing slum management policies in Indonesia, aiming to contribute to sustainable development efforts. The background highlights the significance of addressing slum areas in achieving sustainable urban development goals. The research objective is to unveil the complexities and challenges encountered during the implementation of slum management policies. A qualitative research approach involving interviews, document analysis, and case studies was employed to gain insights into policy formulation, implementation strategies, and their impact on slum communities. The findings reveal the multifaceted nature of slum management, encompassing social, economic, and environmental dimensions. The study identifies the need for integrated and participatory approaches, improved coordination among stakeholders, and targeted interventions to foster sustainable development in slum areas. These findings contribute to the understanding of effective policy implementation and provide insights for policymakers, practitioners, and stakeholders involved in urban development and slum management in Indonesia.